The genetic control of the day- neutral habit in populations of Fragaria vesca (Rosaceae) in Western Siberia - S. O. Baturin (Вавиловский журнал генетики и селекции)
In Western Siberia, intense flowering of Fragaria vesca occurs in the first ten days of June and fruiting takes place from the end of June till early July. During our expeditions investigating natural Fragaria vesca L. populations of Western Siberia in 2002–2013, we registered cases of reflowering, or repeated flowering in August-October. The paper concerns the genetic control of re-flowering in natural populations of Fragaria vesca. The study was conducted with accessions collected in the expeditions and seedlings grown from seeds taken in August-October from natural populations of woodland strawberry reflowering. Genetic analysis of seedlings obtained by self-pollination of collected accessions was also made. It involved 1486 seedlings from plants with seasonal fruiting (representing 32 Western Siberian populations) and 856 seedlings from 10 populations showing reflowering and refruiting. Genetic analysis of reflowering Fragaria vesca plants growing in natural conditions showed that they were usually homozygous for the dominant allele of seasonal fruiting. Reflowering in Fragaria vesca in Western Siberia is considered to be a provisional response of the genotype to certain growth conditions specific for a particular vegetation season. The only woodland strawberry population in the foothills of Kuznetsk Alatau displayed plants heterozygous for fruiting habit. Segregation in the progeny of self-fertilized plants from this population evidences monogenic control of day neutrality with a recessive type of inheritance. Its nature is similar to that in Alpine Fragaria vesca populations.